Potomek króla Salomona na tronie oraz japońskie inspiracje: Konstytucja Cesarstwa Etiopii z 1931 r. - Szklarczyk, Paweł (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
The first modern Ethiopian constitution was promulgated in 1931. It established a constitutional monarchy, however it retained a strong position of the monarch. The analysis of the structure and content of the Ethiopian constitution clearly indicates that it is a case of reception of the Meiji Constitutiona (1889). This article aims to present an outline of the regulations contained in the Constitution of the Empire of Ethiopia by showing its most visible similarities to the Meiji Constitution.
Keywords: constitution; emperor; Ethiopia; Japan; Haile Selassie; Meiji